2002
DOI: 10.1002/1521-4141(200212)32:12<3576::aid-immu3576>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of pro-apoptotic intron 4-retaining soluble HLA-G1 by human villous trophoblast

Abstract: One major materno‐fetal interface in the human placenta is constituted by the syncytiotrophoblast, in contact with maternal blood of the intervillous space, which derives from differentiation and fusion of the villous cytotrophoblast (vct). In the present work, we purified vct from term placenta by depleting HLA class I‐ and class II‐positive cells. We found by RT‐PCR that both soluble intron 4‐retaining HLA‐G1 (sHLA‐G1) and HLA‐G2 isoforms were transcribed in purified vct. Using different HLA‐G‐specific mAb, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(60 citation statements)
references
References 44 publications
1
54
1
4
Order By: Relevance
“…Even though in our system, membrane-bound HLA-G1 had a vastly predominant inhibitory effect over that of sHLA-G1, it was shown that sHLA-G1 induced the apoptosis of activated CD8 ϩ natural killer and T cells (37,38). It is therefore possible that HLA-G1 shedding by HLA-G1 APCs induce a long-term antigen-specific unresponsiveness apparently similar to T cell anergy.…”
Section: Hla-g1mentioning
confidence: 55%
“…Even though in our system, membrane-bound HLA-G1 had a vastly predominant inhibitory effect over that of sHLA-G1, it was shown that sHLA-G1 induced the apoptosis of activated CD8 ϩ natural killer and T cells (37,38). It is therefore possible that HLA-G1 shedding by HLA-G1 APCs induce a long-term antigen-specific unresponsiveness apparently similar to T cell anergy.…”
Section: Hla-g1mentioning
confidence: 55%
“…We focused our study on the two main HLA-G isoforms, namely the membrane-bound HLA-G1 and the soluble HLA-G5 proteins. In physiological conditions, both isoforms are expressed at the fetal-maternal interface in trophoblast where they act as specific immunosuppressors and prevent the rejection of the semiallogeneic fetus by the maternal immune system [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Initially detected at the fetal-maternal interface, the expression of HLA-G protects the fetal semi-allograft from rejection by the mother's immune system [9][10][11]. In non-pathological conditions, HLA-G expression is restricted to immunoprivileged sites such as trophoblast and thymus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, recognition of HIV-1-infected cells by CD8 + CTL and/or natural killer cells (Lopez-Botet et al, 2000) and survival of these cells may, at least in part, depend on HLA-G1 expression levels. Future experiments will determine whether changes in the expression of different isoforms of HLA-G1, including soluble, could limit or favour HIV spreading through the host or the placenta, where HLA-G1 is highly expressed (Le Bouteiller & Blaschitz, 1999;Solier et al, 2002;Ishitani et al, 2003).…”
Section: Discussionmentioning
confidence: 99%